Relationship between Household Tuberculosis and Socioeconomic and Bioenvironmental Factors: A Statistical Model Approach Using NFHS-5 Data - Anant Kumar Pandey; Himansu K. Chaturvedi; Pooja Choraria (Indian Journal of Community Medicine)
Tuberculosis (TB) remains a pressing global health concern, particularly in low- and middle-income countries like India, where it poses significant challenges to public health. This study investigates the socioeconomic and bioenvironmental determinants of TB at a household’s level using data from the fifth round of the National Family Health Survey conducted in India between 2019 and 2021. The study utilizes a comprehensive approach, including univariate, bivariate, and regression analyses, to explore the relationship between TB prevalence and various independent factors. Regression models, including binomial, Poisson, and negative binomial, are employed to elucidate the predictors of TB. The data reveal higher TB prevalence in rural areas compared to urban areas, with households headed by males exhibiting a greater prevalence. Socioeconomic factors such as possession of a Below Poverty Line card and access to electricity are significantly associated with household TB status. Additionally, bioenvironmental factors such as type of cooking fuel and water sanitation measures play crucial roles in shaping TB dynamics within households. The findings underscore the complex interplay between socioeconomic status, living conditions, and bioenvironmental factors in influencing household TB risk. This study provides valuable insights into the socioeconomic and bioenvironmental determinants of TB prevalence at a household’s level, informing evidence-based policy and intervention strategies aimed at reducing TB burden and advancing progress toward global TB elimination goals. Moreover, housing infrastructure, promoting clean energy access, and gender-sensitive approaches can enhance TB control efforts and promote community health.